Challenges and Solutions of Free and Open Source Software Documentation: A Systematic Mapping Study - Pinho, Giniele; Caçula, Aguiar Jeová; Costa, Lucas; Wiese, Igor; Araújo, Allysson Allex (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3307, 2024)
Software documentation is a relevant process for delivering quality software, as it assists stakeholders in using, understanding, maintaining, and implementing software productively. However, notable particularities emerge when investigating the context of Free and Open Source Software (FOSS) projects, which require special attention. Therefore, through a Systematic Mapping Study (SMS), this work aims to map the challenges and solutions regarding software documentation in FOSS based on the last ten years of scientific research (published between 2013 and 2023). From an initial set of 1271 papers, 12 primary studies were identified from which it was possible to categorize five challenges (Collaboration, Quality, Incompleteness, Maintainability, and Categorization) and three general perspectives of solutions (Strategic Use of README, Adoption of Artificial Intelligence, and Support Tools & Approaches). As an academic contribution, we provide an SMS revealing a set of challenges and solutions related to software documentation, a topic still underexplored in the FOSS research context. From a practical and industrial standpoint, this paper promotes a reflection on the use of documentation in FOSS projects, echoing challenges and solutions that can contribute to improving the quality of documentation.